Research on electrochemical characteristics and heat generating properties of power battery based on multi-time scales. (15th February 2023) - Wu, Tingting; Wang, Changhong; Hu, Yanxin; Liang, Zhixuan; Fan, Changxiang
Abstract: A comprehensive understanding of the mechanisms of battery is essential for the design of thermal management systems. In this work, a second-order equivalent circuit model considering the hysteresis effect of the battery was developed, and a combined EIS and HPPC characterization method was used for parameter identification. The results showed that the combining EIS and HPPC parameter measurement methods could extract and analyze the parameters of the battery with different time scales and improve the accuracy of the model. It was found that the polarization internal resistance ( R 1 and R 2 ) of the battery shows a stronger temperature dependence than the ohmic internal resistance at low temperatures, with R 1 being about 170 times higher at low temperatures (10 °C) than high temperatures (50 °C). At the same temperature, τ 2 was approximately 100 times larger than τ 1, which was two orders of magnitude difference between τ 1 and τ 2 . In addition, the dynamic heat generation results showed that the heat generation rate of the battery increases with decreasing temperature. At 3C discharge rate, the heat generation rate of the battery at low temperature (−10 °C) was about 1.5 times higher than at room temperature (25 °C). Highlights: The time-scale information in the battery is extracted and analyzed. Relationships between internal parameters and kinetic processes were established. The dynamic heat generation process of the battery was studied.